If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2p + -8 + 6p + 4 = 0 Reorder the terms: -8 + 4 + 2p + 6p = 0 Combine like terms: -8 + 4 = -4 -4 + 2p + 6p = 0 Combine like terms: 2p + 6p = 8p -4 + 8p = 0 Solving -4 + 8p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 8p = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 8p = 0 + 4 8p = 0 + 4 Combine like terms: 0 + 4 = 4 8p = 4 Divide each side by '8'. p = 0.5 Simplifying p = 0.5
| 4.5x+5=3.5x | | 10x-3=12x+13 | | 3r-4+6r+3= | | 7r-8q+1r-3q= | | 7r-5s-1r-2s= | | 7s-5+5s+8= | | 1q-3+2q+2= | | x+2x-3+2x+6=83 | | 6s-2p-8s-3p= | | 6v^2+13v=5 | | 9q-2p+1q-1p= | | 4x+34=180 | | 3s-13s=-12 | | 5x=x+44 | | -6x+9=16 | | 3s-7+8s+4= | | 2h^2-9h=5 | | b^2+7b=8 | | y^2+6y-247=0 | | 7s-8+4s+6= | | 4s-9p-5s-3p= | | (2x^2-x-9)=0 | | 5p^2+29p-6=0 | | 9r+5r= | | 3z=14+10z | | 8r-2q+4r-7q= | | 2p-5q+4p-4q= | | 2q-9p+1q-2p= | | 5q-6+8q+7= | | 2x+48=3x+11 | | 5a+12=2 | | t^2=2t^2-5t+6 |